Collaborative Settings Increase Dishonesty - Du, Youhong; Ma, Weina; Sun, Qingzhou; Sai, Liyang (Frontiers in Psychology, 2021)
The present study examines whether collaborative situations make individuals more dishonest. It also considers how this dishonesty unfolds over time. To address these questions, we employed a sequential dyadic die-rolling task in which two participants in a pair receive a payoff only if both report the same die-roll outcome. On each trial, one participant (role A) rolled a die first and reported the outcome. Then, the second participant (role B) was informed of A’s reported number, rolled a die as well and reported the outcome. If their reported outcomes were identical, both of them received a reward. We also included an individual condition in which an individual subject rolled a die twice and receive a reward if he/she reported the same die-roll outcome. We found that B lied significantly more than participants in individual condition, whereas A lied as much as participants in individual condition. Furthermore, when collaborating, more and more participants (both A and B) became dishonest as the game progressed, whereas there was no such trend among participants during the individual condition. These findings provide evidence indicating that collaborative settings increase dishonesty and that this effect becomes more evident as the collaboration progress.